同步带传动纵向振动的分析 - 杨玉萍; 钱永明; 沈世德 (Jixie chuandong)
The axial vibration models and the equation of motion of the transmission timing-belt are established in this paper. According to the equation, the natural frequency and the forced vibration when pulley is eccentric are obtained.